The Influence Of Personal Experience On The Poetry Of Byron And Lermontov In The Modern Day - Ruzibayeva Aziza Kahramanovna (Open Academia, 2024)
This article explores the profound influence of personal experience on the poetry of Lord Byron and Mikhail Lermontov, examining how their individual struggles, relationships, and emotional turmoil shaped their works. By analyzing key poems and the biographical context of both poets, this study highlights the relevance of their experiences in the modernday literary landscape. The article argues that their portrayal of introspection, existential angst, and romantic longing continues to resonate with contemporary readers and writers, influencing modern poetic expressions and themes
Keywords: Byron; Lermontov; Romantic poetry; individualism